2012
DOI: 10.1364/oe.20.021702
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of total absorption of light by two-dimensional channel and hole array gratings

Abstract: A detailed study of light absorption by silver gratings having two-dimensional periodicity is presented for structures constructed either of channels or of holes with subwavelength dimensions. Rigorous numerical modelling shows a systematic difference between the two structures: hole (cavity) gratings can strongly absorb light provided the cavity is sufficiently deep, when compared to the wavelength, whereas very thin channel gratings can induce total absorption. A detailed analysis is given in the limit when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…For the metallic grooves, there are two possibilities envisaged: one is with isolated metal blocks and the other is with continuous metal but isolated air holes. It is confirmed that the structure with isolated metal blocks is the evolution scheme from the 1D array of grooves [128,129]. However, the 2D array of metallic holes suffers the cut-off condition on hole sizes because cavity modes are excited inside the holes.…”
Section: Review Articlementioning
confidence: 91%
See 1 more Smart Citation
“…For the metallic grooves, there are two possibilities envisaged: one is with isolated metal blocks and the other is with continuous metal but isolated air holes. It is confirmed that the structure with isolated metal blocks is the evolution scheme from the 1D array of grooves [128,129]. However, the 2D array of metallic holes suffers the cut-off condition on hole sizes because cavity modes are excited inside the holes.…”
Section: Review Articlementioning
confidence: 91%
“…Here, because they can be described as an equivalent layer with effective constitutive parameters of unusual values, they are named plasmonic metamaterial absorbers [29,111,132,[145][146][147][148][149]. Note that the optically deep metallic grooves have also been treated as metamaterial absorbers in many works [22,111,130,150,151]. In addition, some reports also use 1D metal/dielectric stacks [21], 2D metallic nanowires [52,152] or 3D metallic nanoparticles [32,153] to form metamaterial absorbers.…”
Section: Metamaterials Absorbersmentioning
confidence: 99%
“…There are few technical and regulatory challenges associated with the micro-grid implementation with smart grid [129]. Micro-grids are subjected to frequency and voltage problems caused by imbalance between demand and supply [130], [131]. These problems can become severe in cases where the 'plug-and-play' feature is provided to connect and disconnect the generators [132].…”
Section: Issues and Challengesmentioning
confidence: 99%
“…Increasing complexity in the system also necessitates integration of appropriate protection devices. In micro-grid infrastructure, the protection system is different from the traditional power system as it involves bidirectional flow of power [131]. More about the micro-grid protection schemes are presented in Basak et al, Mirsaeidi et al and Che et al [136]- [138].…”
Section: Issues and Challengesmentioning
confidence: 99%
“…In elongated elliptical and rectangular holes, this dependence is stronger than in circular or square ones. The rich phenomenology of both single rectangular apertures [10][11][12][13][14][15][16][17][18] and rectangular hole arrays [12,[19][20][21][22][23] have been applied to develop single molecule fluorescence [24], spectral and polarization sensing [25][26][27][28], perfect absorption [29], and probing the optical magnetic field [30,31].…”
Section: Introductionmentioning
confidence: 99%